Determinanty realizacji oczekiwań społecznych w zakresie planowania i zagospodarowania przestrzennego w gminach - Tabernacka, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
One can distinguish legal, factual and political determinants of implementation of social expectations in the spatial planning and land development area. Because of the fact that competences in the area of spatial planning and land development in Poland are used primarily at the communes level, above mentioned expectations can find their realization in relations between communes public bodies and citizens. Commune as the tier of local self government, which is the closest to citizens, should provide to its inhabitants the broad right of participation in spatial planning and land development and should allow to create a forum for making agreements not only between citizens but also between citizens and public authorities. Putting here participation democracy and mediation in practice is possible.
Keywords: spatial planning; development planning; socially justified interest; social participation